An investigation for improving dry anaerobic digestion of municipal solid wastes by adding biochar derived from gasification of wood pellets. (March 2022) - Salehiyoun, Ahmad Reza; Zilouei, Hamid; Safari, Mohammad; Di Maria, Francesco; Samadi, Seyed Hashem; Norouzi, Omid
Abstract: In this study, the effect of biochar addition derived from a downdraft fixed-bed gasifier on the performances of dry anaerobic digestion of the Organic Fraction of Municipal Solid Waste (OFMSW) was investigated at a high organic load of (1) the source segregated OFMSW (16 and 26% TS) and (2) the source segregated OFMSW replaced with 15% garden waste (22.2% TS). Adding biochar effectively enhanced the rate and yield of biomethane (up to 36.6%), controlled acidification, and shortened lag phase in both feedstocks at high organic loads up to 136.9 gVS/L. Execution of dry anaerobic digestion for source-separated OFMSW without acidification can only be achieved by more than 30 g/L biochar dosage, which is better to run in a semi-solid state (16% TS). However, the synergistic effects at higher biochar doses were not palpable. OFMSW with a higher C/N ratio yielded more limited benefits, as inhibitory volatile fatty acids were further controlled in the early days. This study could promise the integration of gasification and dry anaerobic digestion to enhance the biogas production efficiency at high organic loads, although more researches should be done under continuous conditions.